The Relationship Between Pregnant Women's Awareness of Pregnancy Risk Factors and Their Readiness for Childbirth at Dr. Hi. Zainal Umar Sidiki Regional Hospital, Gorontalo - Sulastri Kaluku; Reny Retnaningsih (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2026)
Pregnant women's readiness for childbirth is an important factor in preventing delays in the management of obstetric complications. One of the main determinants of childbirth readiness is the level of pregnant women's awareness of pregnancy risk factors that can endanger the mother and fetus. This study aims to analyze the relationship between pregnant women's awareness of pregnancy risk factors and their readiness for childbirth in the working area of Dr. Hi. Zainal Umar Sidiki Regional Hospital, North Gorontalo Regency. This study used an observational analytical design with a cross-sectional approach. The study sample consisted of 32 pregnant women selected using a total sampling technique. Data were collected in March–May 2025 using a structured questionnaire to measure the level of awareness of pregnancy risk factors and readiness for childbirth. Data analysis was carried out descriptively and inferentially using the Chi-square test. The results showed that most pregnant women had a moderate level of awareness of pregnancy risk factors and were in the category of being ready for childbirth. Inferential analysis showed a very significant relationship between the level of awareness of pregnant women regarding pregnancy risk factors and their readiness for childbirth (p < 0.001). It can be concluded that the higher the level of awareness of pregnant women regarding pregnancy risk factors, the better the mother's readiness for childbirth. These findings emphasize the importance of strengthening antenatal education focused on increasing awareness of pregnancy risks as a strategy to improve childbirth preparedness and support efforts to prevent maternal complications.